Portocaval shunt can optimize transhepatic flow following extended hepatectomy: a short-term study in a porcine model - Golriz, Mohammad; Majlesara, Ali; Khajeh, Elias; Rezaei, Nahid; Saffari, Arash; Arwin, Jalal; Hafezi, Mohammadreza; Sakka, Saroa el; Abbasi Dezfouli, Sepehr; Emami, Golnaz; Ramouz, Ali; Mehrabi, Arianeb (Scientific reports, 2022)
The aim of this study was to evaluate whether the portocaval shunt (PCS) corrects these unwanted changes in transhepatic flow after extended hepatectomy (EH). Forty female Landrace pigs were divided into two main groups: (A) EH (75%) and (B) no EH. Group A was divided into 3 subgroups: (A1) EH without PCS; (A2) EH with side-to-side PCS; and (A3) EH with end-to-side PCS. Group B was divided into 2 subgroups: (B1) side-to-side PCS and (B2) end-to-side PCS. HAF, PVF, and PVP were measured in each animal before and after the surgical procedure. EH increased the PVF/100 g (173%, p < 0.001) and PVP (68%, p < 0.001) but reduced the HAF/100 g (22%, p = 0.819). Following EH, side-to-side PCS reduced the increased PVF (78%, p < 0.001) and PVP (38%, p = 0.001). Without EH, side-to-side PCS reduced the PVF/100 g (68%, p < 0.001) and PVP (12%, p = 0.237). PVP was reduced by end-to-side PCS following EH by 48% (p < 0.001) and without EH by 21% (p = 0.075). PCS can decrease and correct the elevated PVP and PVF/100 g after EH to close to the normal values prior to resection. The decreased HAF/100 g in the remnant liver following EH is increased and corrected through PCS.